5x-(7)=7x-(17)

Simple and best practice solution for 5x-(7)=7x-(17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(7)=7x-(17) equation:


Simplifying
5x + -1(7) = 7x + -1(17)

Multiply -1 * 7
5x + -7 = 7x + -1(17)

Reorder the terms:
-7 + 5x = 7x + -1(17)

Multiply -1 * 17
-7 + 5x = 7x + -17

Reorder the terms:
-7 + 5x = -17 + 7x

Solving
-7 + 5x = -17 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-7 + 5x + -7x = -17 + 7x + -7x

Combine like terms: 5x + -7x = -2x
-7 + -2x = -17 + 7x + -7x

Combine like terms: 7x + -7x = 0
-7 + -2x = -17 + 0
-7 + -2x = -17

Add '7' to each side of the equation.
-7 + 7 + -2x = -17 + 7

Combine like terms: -7 + 7 = 0
0 + -2x = -17 + 7
-2x = -17 + 7

Combine like terms: -17 + 7 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| -3x-6=18forx | | 10x+4x+3+7=9x+3+4x | | 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 | | 9i*12i= | | 2(x+1)+5=-4(x-2) | | 5(3x+7)=-19+39 | | 17+p=30 | | 4+5lnx=19 | | 5u^3+4u^2-25u-20=0 | | 5(5x+2)-5= | | 4(-6x-2)+10=8(-3x-1)+14 | | n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 | | -344=8(8v-3) | | (X^3-7)/(x-2) | | 18x=288 | | 1(-4x-5)+7=4(-1x-4)+18 | | x+5=8+x | | s^2=323 | | 3+3x=3x+2 | | 3/4(2?3M)=24 | | 26/y=2 | | -147=3k-3(8k+7) | | -1(x+3)-3=-6(x+8) | | 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 |

Equations solver categories